2006
DOI: 10.1007/s10533-006-9019-5
|View full text |Cite
|
Sign up to set email alerts
|

The global-scale temperature and moisture dependencies of soil organic carbon decomposition: an analysis using a mechanistic decomposition model

Abstract: Since the decomposition rate of soil organic carbon (SOC) varies as a function of environmental conditions, global climate change is expected to alter SOC decomposition dynamics, and the resulting changes in the amount of CO 2 emitted from soils will feedback onto the rate at which climate change occurs. While this soil feedback is expected to be significant because the amount of SOC is substantially more than the amount of carbon in the atmosphere, the environmental dependencies of decomposition at global sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 59 publications
8
104
2
1
Order By: Relevance
“…In contrast to our findings, a recent modelling study, based on current litter 470 input rates and soil-C stocks, estimated that the global temperature sensitivity of SOM 471 decomposition equated to a Q 10 value of just 1.37 (Ise and Moorcroft, 2006). SOM 472 accumulation is the result of small differences between inputs and outputs, and links 473 between plant productivity and soil respiration, which probably cannot be represented 474 simply by differences in current litter input rates (Ise and Moorcroft, 2006), may 475 affect the relationship between temperature and SOM accumulation.…”
Section: Losses 469contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, a recent modelling study, based on current litter 470 input rates and soil-C stocks, estimated that the global temperature sensitivity of SOM 471 decomposition equated to a Q 10 value of just 1.37 (Ise and Moorcroft, 2006). SOM 472 accumulation is the result of small differences between inputs and outputs, and links 473 between plant productivity and soil respiration, which probably cannot be represented 474 simply by differences in current litter input rates (Ise and Moorcroft, 2006), may 475 affect the relationship between temperature and SOM accumulation.…”
Section: Losses 469contrasting
confidence: 99%
“…SOM 472 accumulation is the result of small differences between inputs and outputs, and links 473 between plant productivity and soil respiration, which probably cannot be represented 474 simply by differences in current litter input rates (Ise and Moorcroft, 2006), may 475 affect the relationship between temperature and SOM accumulation. In our model, the 476 input rate remained constant throughout but one consequence of higher decomposition 477 rates could be increased nutrient availability, which could feedback on plant 478 productivity and therefore the rate of C input to the soil.…”
Section: Losses 469mentioning
confidence: 99%
“…The former value is very close to the overall mean values of 2.3 reported by Lenton and Huntingford (2003), whereas the latter value is closer to the overall mean value of 1.3 reported by Ise and Moorcroft (2006).…”
Section: Sensitivity Of Soil Respiration To Temperaturesupporting
confidence: 82%
“…1 Glucosidase (a, b, g) and protease (c-f, h) (Craine et al 2010;Fierer et al 2006;Ise and Moorcroft 2006;Townsend et al 1992). Enzymatic activities in soil and sediment samples measured during the present study showed maximum rates at temperatures above 50°C.…”
Section: Resultsmentioning
confidence: 53%
“…Generally, enzymatic activity shows maxima at a temperature slightly higher than the optimum for growth of a microorganism (Burton et al 2002;Kube et al 2013;Madigan et al 2003;Tang et al 2010). However, enzymatic activity sharply decreases at increasing temperatures beyond its optimum (Ise and Moorcroft 2006;Madigan et al 2003). As a consequence, increasing temperatures above the experimental threshold for mesophiles (i.e., temperatures for optimum microbial activity and growth) should reflect highly diminished microbial enzymatic activities and consequently a decrease of the estimates for the expected decomposition of organic matter in soils (Conant et al 2011;Davidson and Janssens 2006).…”
Section: Introductionmentioning
confidence: 99%